Analisis Tekanan Pembriketan Pada Alat Pencetak Briket Hydraulic Press - Rahmad Setiyoadi, Retno Eka Pramitasari (Jurnal MOTION ( Manufaktur, Otomasi, Otomotif, dan Energi Terbarukan), 2022)
Bricket is an alternative fuel made of various fuel mixed into one and formed into solid fuel according to needs. Usually the basic ingredient of briket is a chain of grain, corn cobbler and sugar cane. In this research will be designed a Bricket press tool with hydraulics as the main source of his movers. Research designed to build a Briket Press printer using R&D method (Research and development). On the process of designing initiated with the design of the device covering, design skeletons, prints, pressing pads, closing the prints, and holding the prints. Testing the device using a descriptive method by asking a few questions or angles to validator. The result of the pressure test and time it takes for a discharge is 150 kg/cm2/2133 psi. The time it takes is 246 seconds/ 04.10 minutes. The result of the functional and functional test results that were validated by 2 validators that were 93.5% for the proper test. The functional test results are 93%. The average large on the testing of functional and functional property testing is 93.25% categorized very well.